2012
DOI: 10.1002/ejoc.201200198
|View full text |Cite
|
Sign up to set email alerts
|

Dioxirane‐Mediated Heterogeneous Epoxidations with Potassium Caroate: A Solid Catalyst Bearing Anchored Ketone Moieties

Abstract: A new hybrid material (3) consisting of trifluoromethyl ketone (TFMK) moieties, immobilized on silica through an appropriate spacer, was synthesized and characterized. Lacking easily oxidizable functionalities in the spacer chain, this material proved to be an excellent catalyst in heterogeneous epoxidations with potassium caroate (KHSO5), surpassing other reported catalysts in performance and stability. The efficiency of silica‐supported catalyst 3 could be assessed upon carrying out the selective dioxirane‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Oxidation of 3-hexyne ( 8 ) afforded smoothly the expected 3,4 hexanedione ( 8a ) ( Table 1 , run 5), a very interesting result if considering that 1,2-diones are valuable building blocks in organic synthesis, especially as precursors of several heterocyclic compounds [ 29 , 30 , 31 ]. This representative example shows how the novel catalyst is more reactive than those reported previously [ 16 , 20 ], including also the methyl perfluoroheptyl ketone 2 used under homogeneous conditions [ 20 ].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Oxidation of 3-hexyne ( 8 ) afforded smoothly the expected 3,4 hexanedione ( 8a ) ( Table 1 , run 5), a very interesting result if considering that 1,2-diones are valuable building blocks in organic synthesis, especially as precursors of several heterocyclic compounds [ 29 , 30 , 31 ]. This representative example shows how the novel catalyst is more reactive than those reported previously [ 16 , 20 ], including also the methyl perfluoroheptyl ketone 2 used under homogeneous conditions [ 20 ].…”
Section: Resultsmentioning
confidence: 95%
“…Reaction parameters were calibrated for processing 1 mmol of alkene in the presence of ketone ( 2 ) (in the range of 5–15%) and caroate (4 mmol) as an oxygen source. Reaction medium and the other settings were chosen to be quite similar to those generally adopted in the dioxirane epoxidation in situ; in particular, the conditions used in the case of silica functionalized with trifluoroacetyl moiety [ 16 ]. Despite the heterogeneous conditions, supported organocatalysts proved to be highly active, providing almost all higher conversions in shorter reaction times respect to those obtained with methyl perfluoroheptyl ketone ( 2 ) alone ( Table 1 , runs 3–4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the in situ method, we found that in the reactions carried out with TFDO the ketonei sn ot appreciably consumed, as it simply acts as ac atalystt oa ctivatet he inexpensive caroateo xidant. [42] However,c ovalenta ttachment of the trifluoromethyl ketone moiety to as olid matrix [43,44] might provide the additional advantage of easy recycling of the catalyst.…”
Section: Regioselective Càhbondoxyfunctionalization In Nonnatural Tarmentioning
confidence: 99%
“…In fact simple [18] or supported ketones [20] and optical active ketones as precursors of chiral dioxiranes in situ [21, 22] could be used in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%